2012
DOI: 10.2174/156802612799436669
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Therapeutic Applications of Peroxisome Proliferator- Activated Receptors

Abstract: Peroxisome proliferator-activated receptors (PPARs) are ligand dependent transcription factors. The three mammalian PPARs are key regulators of fatty acid and lipoprotein metabolism, glucose homeostasis, cellular proliferation/ differentiation and the immune response. PPARs are therefore important targets in the treatment of metabolic disorders such as insulin resistance and type 2 diabetes mellitus, and are also of interest in relation to chronic inflammatory diseases such as atherosclerosis, arthritis, chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 431 publications
(651 reference statements)
1
46
0
Order By: Relevance
“…Peroxisome proliferator activated receptor gamma (PPARg) expression was also measured as the effects of PPARg on adipocytes increase insulin sensitivity and the production of cytokines that regulate glucose homoeostasis (Floyd and Stephens 2012). Expression of acetyl CoA carboxylase 1 (Acc1) and carnitine-palmitoyl transferase 1a (Cpt1a) was determined as these are downstream targets of PPARa (Menendez-Gutierrez et al 2012).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Peroxisome proliferator activated receptor gamma (PPARg) expression was also measured as the effects of PPARg on adipocytes increase insulin sensitivity and the production of cytokines that regulate glucose homoeostasis (Floyd and Stephens 2012). Expression of acetyl CoA carboxylase 1 (Acc1) and carnitine-palmitoyl transferase 1a (Cpt1a) was determined as these are downstream targets of PPARa (Menendez-Gutierrez et al 2012).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…It should be taken into account that FAAH, besides anandamide, hydrolyses other N-acylethanolamines, such as palmitoylethanolamide (PEA) and oleoylethanolamide (OEA) (Bisogno et al, 2002), which in turn activate PPARs receptors. PPARs are a nuclear hormone receptor family of and their target genes are involved in the maintenance of both metabolism and energy homeostasis, inflammation, and cell differentiation (Friedland et al, 2012; Menendez-Gutierrez et al, 2012; Neher et al, 2012; Poulsen et al, 2012; Alexander et al, 2015). In the last decade, growing evidence showed that PPARs are bound and activated by endocannabinoids, endocannabinoid-like compounds, phytocannabinoids and synthetic cannabinoid postulating a potential roles for PPAR activation in the physiological effects of cannabinoids (Liu et al, 2003; O’Sullivan, 2007; O’Sullivan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, endocannabinoids, and their analogs, show binding affinity for other receptor families beyond the cannabinoid receptors, including the peroxisome proliferator-activated receptors (PPARs) (Fu et al, 2003; Bouaboula et al, 2005; O’Sullivan, 2007; Campolongo et al, 2009a; Luchicchi et al, 2010), and the transient receptor potential channels, especially vanilloid receptors transient receptor potential cation channel subfamily V member 1 (TRPV1) (Zygmunt et al, 1999; Di Marzo and De Petrocellis, 2010). PPARs are family of a nuclear hormone receptor (PPAR-α, PPAR-β/δ, and PPAR-γ) which regulate several biological functions such as lipid homeostasis (Friedland et al, 2012; Menendez-Gutierrez et al, 2012; Neher et al, 2012; Poulsen et al, 2012; Alexander et al, 2015). Particularly, PPAR-α is expressed in the hippocampus and regulates the expression of neuronal cAMP-response-element binding protein (CREB), a key regulator of memory formation (Roy et al, 2013, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The interest in studying the effects of nsSNPs on structural stability and dynamic properties of PPARγ derives from the involvement of this nuclear receptor in a variety of biological processes such as adipocyte differentiation and insulin sensitization, as well as cellular differentiation and development and carcinogenesis [14]. Notably, PPARγ functions have been linked to several pathologies, ranging from metabolic disorders to cardiovascular disease, chronic inflammation, neurodegenerative disorders, and cancer [51,52]. PPARs ligands and other agents influencing PPAR signaling pathways have been shown to display chemopreventive potential by mediating tumor suppressive activities in a variety of human cancers and could represent novel targets to inhibit carcinogenesis and prevent tumor progression [53].…”
Section: Discussionmentioning
confidence: 99%